Analysis of Karate Sports Achievement Management in the Sangkareang Dojo 93 - M Khaerul Bayyani; Lalu Sapta Wijaya Kusuma; Johan Wahyudi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
functions (Planning, Organizing, Actuating, And Controlling) on the performance of karate athletes at Dojo Sangkareang 93, East Lombok. The study used a descriptive quantitative approach involving 50 respondents (5 coaches and 45 senior athletes) as a saturated sample. Data were collected through a closed questionnaire that had been tested for validity and reliability (α = 0.848), then analyzed using correlation,Pearson Product Moment, multiple correlation, and F test. The results of the study showed that the four management functions were in the very good category. Partially, planning (r = 0.655), organizing (r = 0.631), and supervision (r = 0.638) each had a strong relationship with achievement, while motivating showed a moderate relationship (r = 0.457). Simultaneously, the four management functions had a strong and significant relationship with athlete achievement (R = 0.775; F = 15.040; Sig. 0.001), with a contribution of 60.1% to athlete achievement. This finding confirms that effective achievement coaching is the result of synergy between management functions, with planning as the most determining element.